Cultura ambiental y su implicancia en la conservación de sus recursos naturales en pobladores de la comunidad de Gallito. Distrito de Fernando Lores. 2021 - Vergara Calle, Pedro Alejandro (2022)
The study was called "Environmental culture and its implication in the conservation of its natural resources in residents of the Gallito community. District of Fernando Lores. 2021=. Having as objective "Determine what is the level of environmental culture and its implication in the conservation of its natural resources of the inhabitants of the Gallito study farmhouse. The non-experimental, quantitative research design was used. The research work is descriptive-transversal. A simple probabilistic sample was used, where 220 people who live in the study community were chosen. The results were developed through descriptive statistics, being: Applying the Rho Spearson test and relating it to the proposed hypothesis, this is rejected, since the inhabitants of Gallito have a low or deficient environmental culture. Regarding environmental attitudes, it is found that they are acceptable or good (29.1%) to very acceptable or excellent (70.9%) measured with the Liker scale. In environmental behavior there are values that go from good (80%) to excellent (16.4%). In environmental knowledge it can be seen that it is regular (79.5%) to good (20.5%). For the variable conservation of natural resources and knowledge of the ANP, in this population, results were obtained evaluated with a Liker scale, good (67.3%) and regular (32.7%). It is concluded by stating that, according to the perception of the inhabitants on environmental culture, they refer that it is part of their natural and cultural environment that they develop and their interrelation with it.